2008
DOI: 10.1111/j.1728-4457.2008.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

International Migration as a Tool in Development Policy: A Passing Phase?

Abstract: This essay examines the recent emergence of migration and development as a major area of policy concern. The focus up to now has been almost entirely upon international migration, which accounts for the minority of people who move. A consensus has emerged that migration can be managed so as to promote development, and the essay critically assesses three of the major areas of concern: remittances, skilled migration, and the diaspora. While welcoming the growing acceptance that migration is no longer seen as neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
186
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(196 citation statements)
references
References 24 publications
0
186
0
8
Order By: Relevance
“…As several authors have indicated, the academic debate on the migration-development nexus is rather segregated [4][5][6][7]23]. On the one hand, there are -migration optimists‖ that build on modernization development theories, valuing the distributive trickle down effects that derive from migration (e.g., remittances, skills).…”
Section: The Opposing Logics Of Migration-development Discussionmentioning
confidence: 99%
“…As several authors have indicated, the academic debate on the migration-development nexus is rather segregated [4][5][6][7]23]. On the one hand, there are -migration optimists‖ that build on modernization development theories, valuing the distributive trickle down effects that derive from migration (e.g., remittances, skills).…”
Section: The Opposing Logics Of Migration-development Discussionmentioning
confidence: 99%
“…The remittances sent back home by overseas migrants is the final fruit cultivated through the hardship they experience in the destination countries (Athukorala, 1992;Wells, 1996;Ilahi & Jafarey, 1999;Wickarmasekara, 2000;Richard et al, 2005;Hull, 2007;Martin, et al, 2007, p. 2;Skeldon, 2008a;Kaur, 2010;Yoeh et al, 2010;Battistella & Binodkhadria, 2011). Eventually, the people in the countries receiving remittance benefit greatly from it, although this income might not be channeled properly and might result in inequality (Jones, 1998a;Jones, 1998b;Mutersbaugh, 2002;Hull, 2007;Skeldon, 2008a;Skeldon, 2008b).…”
Section: Remittances and Its Cumulative Benefitsmentioning
confidence: 99%
“…Contemporary research in Geography recognizes that the relationship between migration and development is critical. For example, many studies of remittances, skilled migration, and brain drain/brain circulation (Skeldon 2008) link migration to the socioeconomic standing of communities, regions, and nations. For some communities, and even some countries, remittances provide a mainstay of the local economy.…”
Section: Linking Internal and International Migrationmentioning
confidence: 99%